Use of Microsoft Excel as Student Value and Data Management at SDIT Al Uswah Pamekasan - Solehah, Nuridhatus; Izzaty, Fika Nuril; Daifi, Ach.; Makkiyah, Rizqi Amalia (Widyagogik, 2025)
This study discusses the use of Microsoft Excel in the management of student grades and data at SDIT Al Uswah Pamekasan. Along with the rapid development of information technology in the Industrial Revolution 4.0 era, educational institutions are required to optimize the use of technology to improve the efficiency of academic administration. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The results of the study indicate that Microsoft Excel is effective for recording daily grades, midterm and final exams, attendance, and student data recapitulation. The use of Excel provides various benefits, such as work efficiency, increased data accuracy, professional data presentation, and encouraging teachers' technological skills. However, there are challenges in the form of digital literacy inequality among teachers and minimal formal training. Therefore, ongoing training and technological assistance are needed to optimize the use of Microsoft Excel in elementary school environments.